An Interim Study of Integrating Spindle, Laser, and Plotter in a CNC Router Machine - Rosidah Jaafar; Norfariza Ab Wahab; Basri Bin Bidin; Mohammad Nor Mustaqim Bin Johari; Kaliswaran A/L Mogal; Megat Iskandar Fedileh (Engineering Science Letter, 2022)
Although there are so many CNC routers that have been created all around the world, when this manuscript was written, an integrated CNC router with multi different functions was still not common. In this work, we proposed, designed, fabricated, and evaluated a low-cost CNC Router machine that can perform numerous tasks (i.e., spindle engraving, laser, and plotter). Although we first employed a market-available CNC machine, we have developed, changed, and improved almost everything of it so that it can run and go through multiple processes in a single coding process with higher accuracy and efficiency. As a result, the proposed machine is adjusted to conduct an integrated operation without making any significant changes. Through the calibration process, we have validated that the proposed system is capable of performing high-accuracy processes. The proposed CNC router has a wide range of applications and can conduct a variety of engraving procedures, including plotting. Furthermore, when the machine is running, the project runs thru the checks on the accuracy analysis through several processes to ensure the accurate accuracy of the three available processes (spindle, laser, and plotter).